Թուրքիայի, Վրաստանի և Ադրբեջանի եռակողմ համագործակցությունը տրանսպորտի ոլորտում - Դավթյան Էրիկ (YSU Journal of International Affairs, 2017)
The paper analyzes the Turkey-GeorgiaAzerbaijan cooperation in the context of the Baku-Tbilisi-Kars railway and defines both foreign and domestic policy goals that each of the three states has associated with the mentioned initiative, as well suggests a periodization of the Turkey-Georgia-Azerbaijan cooperation within the framework of the railway project. The article also presents the steps, taken by Turkey, Georgia and Azerbaijan towards the realization of the Model Highway Initiative Baku-Tbilisi-Batumi-Trabzon.